1997
DOI: 10.1007/s002619900227
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of portal venous invasion by pancreatobiliary carcinoma: value of endoscopic ultrasonography

Abstract: Endoscopic ultrasonography is the most accurate tool for detecting pancreatobiliary carcinomas and assessing portal venous invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 12 publications
1
45
0
7
Order By: Relevance
“…The average tumor size did not differ significantly between the patients with pancreatic cancer diagnosed during the first hospitalization versus after discharge, probably because identifying a tumor on CT became possible only when the tumor diameter grew to more than 15 mm. These results are consistent with previous reports indicating that it is difficult to detect pancreatic tumors smaller than 15 mm by CT (15)(16)(17)(18)(19). Nevertheless, the tumor stages detected during the first hospitalization and in the patients followed by regular examination with CT were earlier than those in the patients not followed.…”
Section: Discussionsupporting
confidence: 83%
“…The average tumor size did not differ significantly between the patients with pancreatic cancer diagnosed during the first hospitalization versus after discharge, probably because identifying a tumor on CT became possible only when the tumor diameter grew to more than 15 mm. These results are consistent with previous reports indicating that it is difficult to detect pancreatic tumors smaller than 15 mm by CT (15)(16)(17)(18)(19). Nevertheless, the tumor stages detected during the first hospitalization and in the patients followed by regular examination with CT were earlier than those in the patients not followed.…”
Section: Discussionsupporting
confidence: 83%
“…N/A: We could not evaluate the distance between the RHA and the bile duct of the tumor site on the pathological specimen because the HA could be separated from the tumor during surgery. by cholangiocarcinoma has been reported as 87-100% (11)(12)(13)(14) for CT, whereas EUS offers 88-100% accuracy for predicting PV invasion and performs better than transabdominal US and angiography in this regard (15)(16)(17) (18) reported on combined vascular resection for hilar cholangiocarcinoma. They found that cancer invasion into the adventitia was present in 80% of the 44 resected portal veins and 40% of the 9 resected hepatic arteries, and concluded that caution should be exercised when planning combined hepatic artery resection, because cancer invasion into the adventitia of the HA occurs in only about half of the patients despite clinical findings of apparent invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The ERCP technique would be superior to other imaging modalities for this purpose. Endoscopic sonography has been reported to detect vascular invasion of the portal vein associated with extrahepatic tumors of the bile duct with a sensitivity greater than that of transabdominal sonography, CT, and angiography [57]. As previously discussed in HCC, interventional procedures for drainage of obstructive jaundice may be resorted to as a preparatory step before transplantation in the patient with hilar CC.…”
Section: Tumor Staging and Road-mappingmentioning
confidence: 96%